Effect of a persuasive message and normative arguments, on advertising attitudes and purchase intention in ecological cosmetics (2020)
This research explores the effect of different persuasive messages on advertising attitudes and purchase intent in organic cosmetics through a factorial experiment in Colombia with 225 subjects. The results indicate that the participants show more positive attitudes towards the announcement and greater intentions of ecological purchase, when the rational message is presented in combination with the appeal to the subjective norm. Likewise, brand intention and recommendation is positively affected when the message is processed rationally in combination with the subjective norm. These findings show that the advertising messages developed to favor the ecological purchase, enhance their persuasive capacity if they are constructed with rational information framed in normative messages. Practical alternatives to encourage responsible consumption in the cosmetics sector are delivered in the discussion.